Transthoracic repair of a traumatic subarachnoid-pleural fistula Transthorakaler Verschluß einer traumatischen subarachnoidalen-pleuralen Fistel - Dosios, Th.; Tzouras, A. G.; Tsaprounis, G. (Neurochirurgia, 1989)
A 21-year old patient developed paraplegia and a subarachnoid-pleural fistula, as a result of gunshot injury. Successful surgical repair of the fistula was achieved via a transthoracic approach.Ein 21jähriger Patient bekam eine Paraplegie und eine subarachnoidale pleurale Fistel nach einer Schußverletzung. Ein erfolgreicher Fistelverschluß wurde auf dem transthorakalen Wege erreicht.
Keywords: Bullet injuries; Subarachnoid-pleural fistula; Transthoracic approach